2017 Interstices Under Construction Symposium: Pattern / Surface - a pursuit of material narratives PROGRAMME - Jenner, Ross; Engels-Schwarzpaul, Tina; Hedges, susan (Interstices: Journal of Architecture and Related Arts)
***